Association between dietary salt intake and reservation of renal function in patients with mild hypertension - Arsalan Khaledifar (ARYA Atherosclerosis, 2015)
BACKGROUND: It is now hypothesized whether restricted salt intake can be a potential precursor to renal dysfunction in mild hypertension state. We aimed to study the association between salt intake and renal function in patients with mild hypertension. METHODS: One hundred consecutive hypertensive Iranian patients (with systolic blood pressure 140-160 mmHg and/or diastolic 90-100 mmHg) who were referred to the hypertension research center, Isfahan, Iran, between 2011 and 2014 for screening of hypertension were assessed. Renal function was assessed by measuring serum creatinine (Cr) and creatinine clearance (CrCl). Daily salt intake was assessed on the basis of 24 h urinary sodium excretion. RESULTS: There was no association between the amounts of sodium intake and serum Cr concentration (r = 0.138, P = 0.174), however, an association was revealed between sodium intake and value of CrCl (r = 0.303, P = 0.003). Multivariable linear regression model showed that sodium intake could effectively predict renal function assessed by CrCl (Beta = 0.070, P = 0.016). CONCLUSION: There is an association between sodium intake and reservation of renal function in mild hypertension state and thus by restriction of dietary salt intake, reserving renal function, and preventing appearance and progression of renal insufficiency in higher degrees of hypertension can be facilitated.